Ductile Compressive Behavior of Biomedical Alloys - Christian Affolter; Götz Thorwarth; Ariyan Arabi-Hashemi; Ulrich Müller; Bernhard Weisse (Metals, 2019)
The mechanical properties of ductile metals are generally assessed by means of tensile testing. Compression testing of metal alloys is usually only applied for brittle materials, or if the available specimen size is limited (e.g., in micro indentation). In the present study a previously developed test procedure for compressive testing was applied to determine the elastic properties and the yield curves of different biomedical alloys, such as 316L (two different batches), Ti-6Al-7Nb, and Co-28Cr-6Mo. The results were compared and validated against data from tensile testing. The converted flow curves for true stress vs. logarithmic strain of the compressive samples coincided well up to the yield strength of the tensile samples. The developed compression test method was shown to be reliable and valid, and it can be applied in cases where only small material batches are available, e.g., from additive manufacturing. Nevertheless, a certain yield asymmetry was observed with one of the tested 316L stainless steel alloys and the Co-28Cr-6Mo. Possible hypotheses and explanations for this yield asymmetry are given in the discussion section.